Clinical aspects and surgical outcomes of pediatric cholesteatoma in a tertiary care teaching hospital - Gupta, Vijay; Mirza, Navid; Gupta, Arindam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Cholesteatoma in children is customarily viewed as a separate and special entity as it presents the otolaryngologist with a verity of diagnostic and therapeutic challenges. The study was planned with objective of studying the clinical aspects and surgical outcomes of pediatric cholesteatoma. Methods: The patients younger than 15 years and diagnosed as congenital cholesteatoma were included in the present study. All the patients underwent thorough clinical examination, laboratory and radiological investigations. Depending on the stage of disease, surgical procedure was decided. All patients were followed-up for at least 12 months after surgery. Results: Total 46 children congenital cholesteatoma (CC) was included in the study. The mean age of diagnosis was 7.08±5.64 years. All the cases have unilateral ear involvement. 14 patients were asymptomatic and CC were found incidental. Patients with CC represented with more commonly with hearing impairment. The CC was most commonly found in the anterosuperior quadrant. All 46 patients with CC underwent operative procedure with transcanal myringotomy was commonest surgical approach. During the 12 month follow-up, 28.86% of patients presented with recurrence of disease. Conclusions:Despite of improved understanding of this disorder with better surgical techniques and skill, high recurrence rate is still major challenge for successful management of CC.